2000
DOI: 10.1108/01443570010314818
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for achieving agility in manufacturing organisations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
0
34

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(290 citation statements)
references
References 4 publications
4
227
0
34
Order By: Relevance
“…As stated earlier, it is somewhat difficult to establish the theoretical rationale for labeling some practices as "agile" despite the fact that they are commonly referred to as this in practice, e.g., metaphor or pair programming. In contrast, each subcomponent of the definition and taxonomy proposed in this study is justified by an extensive discussion of why it can be classified as "agile," drawing on arguments from previous conceptual studies of agility outside the ISD domain (e.g., Goldman et al 1991Goldman et al , 1995Preiss 1997;Dove 1994Dove , 1995Kidd 1994;Zhang and Sharafi 2000).…”
Section: Definition and Taxonomy Of Isd Agilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, it is somewhat difficult to establish the theoretical rationale for labeling some practices as "agile" despite the fact that they are commonly referred to as this in practice, e.g., metaphor or pair programming. In contrast, each subcomponent of the definition and taxonomy proposed in this study is justified by an extensive discussion of why it can be classified as "agile," drawing on arguments from previous conceptual studies of agility outside the ISD domain (e.g., Goldman et al 1991Goldman et al , 1995Preiss 1997;Dove 1994Dove , 1995Kidd 1994;Zhang and Sharafi 2000).…”
Section: Definition and Taxonomy Of Isd Agilitymentioning
confidence: 99%
“…While some research has looked at each of these subconcepts in isolation, they have not been examined collectively within the broader systemic context. The conceptualization developed in this study provides a macro-level view of ISD agility and its subconcepts, and while frameworks of agility exist in other disciplines (e.g., Goldman et al 1991Goldman et al , 1995Preiss 1997;Dove 1994Dove , 1995Kidd 1994;Zhang and Sharafi 2000), this is the first of its kind in ISD.…”
Section: Definition and Taxonomy Of Isd Agilitymentioning
confidence: 99%
“…Christopher (2000, p. 43) also stresses that agility in individual organizations can be significantly hindered by the level of complexity in terms of brands, products, structures and management processes. In developing a model for achieving agility in manufacturing organizations, Zhang and Sharifi (2000) identified a number of "agility providers" (practices, methods, tools, techniques facilitating a capability for agility). As a result of surveying 1,000 companies, and conducting case studies in 12 of them, they concluded that practices related to people and organizational issues were both more effective and important for manufacturers.…”
Section: Agile Vs Lean Supply Chain Modelsmentioning
confidence: 99%
“…Womack et al (1990) described Toyota's operational flexibility as the ability to compete at the same time on delivery performance, quality performance, differentiation, product price, development time, and lead time reduction. Moreover, Zhang and Sharifi (2000) argued that the leanness level of an organization can be assessed through its flexdibility to respond to changes in business environment and market needs. Similarly, Bessant et al (2003) asserted that flexibility is the key to competitive success and encompasses the ability to respond quickly and flexibly to environmental requirements as well as the ability to respond to emerging challenges with innovative reactions and solutions.…”
Section: Flexibility Performancementioning
confidence: 99%